Mast Cells and MCPT4 Chymase Promote Renal Impairment after Partial Ureteral Obstruction - Pons, Maguelonne; Ali, Liza; Beghdadi, Walid; Danelli, Luca; Alison, Marianne; Madjène, Lydia Celia; Calvo, Jessica; Claver, Julien; Vibhushan, Shamila; Åbrink, Magnus; Pejler, Gunnar; Poli-Mérol, Marie-Laurence; et al. (Frontiers in Immunology, 2017)
Obstructive nephropathy constitutes a major cause of pediatric renal progressive disease. The mechanisms leading to disease progression are still poorly understood. Kidney fibrotic lesions are reproduced using a model of partial unilateral ureteral obstruction (pUUO) in newborn mice. Based on data showing significant mast cell (MC) infiltration in patients, we investigated the role of MC and murine MCPT4, a MC-released chymase, in pUUO using MC- (Wsh/sh), MCPT4-deficient (Mcpt4−/−), and wild-type (WT) mice. Measurement of kidney length and volume by magnetic resonance imaging (MRI) as well as postmortem kidney weight revealed hypotrophy of operated right kidneys (RKs) and compensatory hypertrophy of left kidneys. Differences between kidneys were major for WT, minimal for Wsh/sh, and intermediate for Mcpt4−/− mice. Fibrosis development was focal and increased only in WT-obstructed kidneys. No differences were noticed for local inflammatory responses, but serum CCL2 was significantly higher in WT versus Mcpt4−/− and Wsh/sh mice. Alpha-smooth muscle actin (αSMA) expression, a marker of epithelial–mesenchymal transition (EMT), was high in WT, minimal for Wsh/sh, and intermediate for Mcpt4−/− RK. Supernatants of activated MC induced αSMA in co-culture experiments with proximal tubular epithelial cells. Our results support a role of MC in EMT and parenchyma lesions after pUUO involving, at least partly, MCPT4 chymase. They confirm the importance of morphologic impairment evaluation by MRI in pUUO.